2007
DOI: 10.1111/j.1365-2036.2007.03271.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptom overlap in patients with upper gastrointestinal complaints in the Canadian confirmatory acid suppression test (CAST) study: further psychometric validation of the reflux disease questionnaire

Abstract: SUMMARY BackgroundThe reflux disease questionnaire (RDQ) is a short, patient-completed instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
2
15
1
Order By: Relevance
“…Subsequently, a further validation paper appeared [3,8] and RDQ has now been shown to be reliable, valid and responsive to change in patients with GERD symptomatology and those with dyspepsia, making this tool suitable for use in clinical trials and as a guide to patient management also in a broader primary care population with uninvestigated upper GI symptoms [8]. As a matter of fact, RDQ has been used in large randomized controlled trials, such as, for example, the ProGERD study [9].…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, a further validation paper appeared [3,8] and RDQ has now been shown to be reliable, valid and responsive to change in patients with GERD symptomatology and those with dyspepsia, making this tool suitable for use in clinical trials and as a guide to patient management also in a broader primary care population with uninvestigated upper GI symptoms [8]. As a matter of fact, RDQ has been used in large randomized controlled trials, such as, for example, the ProGERD study [9].…”
Section: Discussionmentioning
confidence: 98%
“…The RDQ has recently been documented as a diagnostic tool for GERD in patients consulting with upper gastrointestinal symptoms in primary care [12] and as a means of monitoring treatment response [13,14]. …”
Section: Methodsmentioning
confidence: 99%
“…Each questionnaire had a high Cronbach's alpha coefficient (≥ 0.8), suggesting good reliability. The internal consistency of the RDQ dimensions replicated findings from the original RDQ, as well as other language versions [48,71]. Although test-retest reliability, known-groups validity and responsiveness to change were not assessed, the test-retest reliability of the Chinese versions of the RDQ and SF-36 was previously established in the Shanghai pilot study [27].…”
Section: Discussionmentioning
confidence: 56%
“…A GERD dimension can be obtained by combining the heartburn and regurgitation dimensions, and the epigastric pain dimension is also known as the dyspepsia dimension. There is strong evidence supporting the validity and reliability of the RDQ as a diagnostic tool in primary care [47] and as a measure of treatment response in clinical trials [48,49]. Previous investigators found that a Chinese version of the RDQ tested in 10 hospitals in China was able to identify the presence of reflux symptoms experienced during the previous month [50].…”
Section: Methodsmentioning
confidence: 99%